Prevalence of Methotrexate-Induced Lung Involvement in Psoriasis Patients - Mahvish Aftab Khan, Sajjad Naseer, Qasim Nawaz, Muhammad Israr, Fazal Rehman, Zia Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Seventy five psoriasis patients who visited the Pakistani Institute of Medical Sciences in Islamabad from January 2021 to January 2022 were examined to assess the incidence of methotrexate-induced lung involvement. Long-term methotrexate therapy often results in lung involvement, which may present as pleuritis, pneumonia, fibrosis, and obliterative bronchiolitis. Clinical evaluations and case data were retrospectively reviewed. Out of the Seventy five individuals tested, the results indicate that 15 (15%) had mild to moderate lung involvement, while 4 (4%) had severe lung involvement. In 67% of the patients, there was no discernible lung involvement. The frequency of methotrexate-induced lung involvement at the Pakistani Institute of Medical Sciences is quite low, despite the fact that it is a possible side effect of long- term methotrexate usage for psoriasis patients. If long-term methotrexate usage raises the likelihood of lung involvement in psoriasis patients, further investigation is required. Objectives: Identifying the frequency of methotrexate-induced lung involvement in psoriasis patients seen at the Pakistani Institute of Medical Sciences in Islamabad from January 2021 to January 2022 is the goal of this research. Methods: Seventy five psoriasis patients who were seen between January 2021 and January 2022 at the Pakistani Institute of Medical Sciences (PIMS) in Islamabad were the subject of the research. Lung involvement was evaluated by a retrospective examination of the case files and clinical evaluation, which may have required pulmonary function tests, chest X-rays, or even chest CT scans. There was no discernible lung involvement, mild to moderate lung involvement, severe lung involvement, or no lung involvement at all. Results: Seventy-five individuals were examined; fifteen (15%) had mild to moderate lung involvement, four (4%) had severe lung involvement, and sixty-seven (67%) had no discernible lung involvement. Conclusion: According to the study’s findings, although methotrexate-induced lung involvement is a possible side effect of long-term methotrexate usage for people with psoriasis, it is not very common at the Pakistani Institute of Medical Sciences. 67% of the individuals in the study had no observable lung involvement. If long-term methotrexate usage raises the likelihood of lung involvement in psoriasis patients, further investigation is required. Keyword: Methotrexate, Psoriasis, Lung Involvement, Prevalence, PIMS